Rethinking the definition of major trauma: The need for trauma intervention outperforms Injury Severity Score and Revised Trauma Score in 38 adult and pediatric trauma centers. Issue 3 (September 2019) - Roden-Foreman, Jacob Watkin; Rapier, Nakia R.; Foreman, Michael L.; Zagel, Alicia L.; Sexton, Kevin W.; Beck, William C.; McGraw, Constance; Coniglio, Raymond A.; Blackmore, Abigail R.; Holzmacher, Jeremy; Sarani, Babak; Hess, Joseph C.; et al.
Abstract : BACKGROUND: Patients' trauma burdens are a combination of anatomic damage, physiologic derangement, and the resultant depletion of reserve. Typically, Injury Severity Score (ISS) >15 defines major anatomic injury and Revised Trauma Score (RTS) <7.84 defines major physiologic derangement, but there is no standard definition for reserve. The Need For Trauma Intervention (NFTI) identifies severely depleted reserves (NFTI+) with emergent interventions and/or early mortality. We hypothesized NFTI would have stronger associations with outcomes and better model fit than ISS and RTS. METHODS: Thirty-eight adult and pediatric U.S. trauma centers submitted data for 88, 488 encounters. Mixed models tested ISS greater than 15, RTS less than 7.84, and NFTI's associations with complications, survivors' discharge to continuing care, and survivors' length of stay (LOS). RESULTS: The NFTI had stronger associations with complications and LOS than ISS and RTS (odds ratios [99.5% confidence interval]: NFTI = 9.44 [8.46–10.53]; ISS = 5.94 [5.36–6.60], RTS = 4.79 [4.29–5.34]; LOS incidence rate ratios (99.5% confidence interval): NFTI = 3.15 [3.08–3.22], ISS = 2.87 [2.80–2.94], RTS = 2.37 [2.30–2.45]). NFTI was more strongly associated with continuing care discharge but not significantly more than ISS (relative risk [99.5% confidence interval]: NFTI = 2.59 [2.52–2.66], ISS = 2.51 [2.44–2.59], RTS = 2.37 [2.28–2.46]). Cross-validation revealed that in all cases NFTI's model provided a much better fit than ISS greater than 15 or RTS less than 7.84. CONCLUSION: In this multicenter study, NFTI had better model fit and stronger associations with the outcomes than ISS and RTS. By determining depletion of reserve via resource consumption, NFTI+ may be a better definition of major trauma than the standard definitions of ISS greater than 15 and RTS less than 7.84. Using NFTI may improve retrospective triage monitoring and statistical risk adjustments. LEVEL OF EVIDENCE: Prognostic, level IV. Abstract : Supplemental digital content is available in the text.